Predictive factors for limited health literacy among persons with cirrhosis: A Swedish explorative cross-sectional study - Maria Hjorth; Anna Forsberg (PLoS ONE, 2025)
Introduction Fatigue and altered cognitive capacity are common symptoms following cirrhosis. Patients consider information about cirrhosis difficult to understand. Health literacy levels vary among persons with chronic illnesses, which can hamper participation in and adaptation to treatment, potential restrictions and recommendations. Limited health literacy might also lead to decreased autonomy. Purpose The aim was to explore predictors of limited health literacy among adults with cirrhosis. Materials and methods This cross-sectional study explored health literacy among 167 Swedish adults with cirrhosis, 94 men and 73 women with a median age of 65 years using the ‘Newest Vital Sign’ instrument. Predictors of limited health literacy were examined in relation to patient characteristics and cirrhosis disease events. The study is reported following the STROBE guidelines. Results The prevalence of limited health literacy was 58%. Low education and covert hepatic encephalopathy were associated with limited health literacy (p < 0.05). Conclusion Limited health literacy is common among Swedish adults with cirrhosis. Both covert hepatic encephalopathy and low education might be predictors of limited health literacy. Healthcare providers should tailor their patient education based on the patient’s literacy level to facilitate understanding, learning and self-management.